Exploring Reflective Practice and CPD Perceptions Among Pre-Service English Teachers in Uzbekistan - Humora, Rakhimova (Pubmedia Jurnal Penelitian Tindakan Kelas Indonesia, 2025)
The purpose of this study is to explore the perceptions and practices of reflective teaching and Continuing Professional Development (CPD) among pre-service English teachers in Uzbekistan. A quantitative, cross-sectional survey design was employed, involving 263 undergraduate students from four universities specializing in English language teacher education. Data were collected through structured questionnaires administered online and analyzed descriptively. The findings show that while most students demonstrate a basic awareness of reflective practice and CPD, their engagement is often irregular and superficial. The most common reflective activities were self-assessment and peer discussions, whereas deeper methods such as learning journals and portfolios were less practiced. Key barriers included lack of time, insufficient training, low confidence in self-assessment, and limited institutional support. Nevertheless, participants acknowledged that reflective practice positively influences their professional growth, particularly when supported by digital tools and guided mentorship. The study concludes that for reflective practice to effectively contribute to teacher professional development, it should be integrated systematically into teacher education curricula. Structured reflection sessions, capacity-building programs, and the incorporation of digital tools are recommended to enhance sustainability and impact.